Feedback (and other dirty words) : why we fear it, how to fix it - Chandler, M. Tamra; Grealish, Laura Dowling (Berrett-Koehler Publishers, 2019)
When it's done right, feedback has been proven to be the most effective means of improving communication and performance for you and your organization. It's too important to give up, and with the help of this book, you'll be able to use it deftly, equitably, and effectively.